2012
DOI: 10.1111/j.1540-5982.2012.01750.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral exposures and systemic solvency risk

Abstract: By introducing a structure of the balance sheets of the banks, which takes into account their bilateral exposures in terms of stocks or lendings, we get a structural model for default analysis. This model allows us to distinguish the exogenous and endogenous default dependence. We prove the existence and uniqueness of the liquidation equilibrium, we study the consequences of exogenous shocks on the banking system and we measure contagion phenomena. This approach is illustrated by an application to the French b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…They found that a single large shock could have devastating effects on the network, but that this was highly dependent on where in the network the shock hit. Gouriéroux, Héam, and Monfort (2012) considered a model that allows interbank investment via shares (like (Elliott, Golub, and Jackson, 2014)) and lending or insurance (like (Eisenberg and Noe, 2001)). Unlike (Elliott, Golub, and Jackson, 2014), they do not introduce discontinuous failure costs.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that a single large shock could have devastating effects on the network, but that this was highly dependent on where in the network the shock hit. Gouriéroux, Héam, and Monfort (2012) considered a model that allows interbank investment via shares (like (Elliott, Golub, and Jackson, 2014)) and lending or insurance (like (Eisenberg and Noe, 2001)). Unlike (Elliott, Golub, and Jackson, 2014), they do not introduce discontinuous failure costs.…”
Section: Previous Workmentioning
confidence: 99%
“…The spread of risk through a financial network is known as financial contagion and has been carefully modeled and studied (Allen and Gale, 2000;Eisenberg and Noe, 2001;Gouriéroux, Héam, and Monfort, 2012;Acemoglu, Ozdaglar, and Tahbaz-Salehi, 2015;Glasserman and Young, 2014;Elliott, Golub, and Jackson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We propose a systemic risk measure based on the WSV and similar financial networks as in Gourieroux et al . () and Elliott et al . (), focusing on how to capture each bank's systemic risk depending on its asset structure and its position in the network.…”
Section: Literature Reviewmentioning
confidence: 87%
“…We base the proposed systemic risk measure on a network framework similar to those in Gourieroux et al . () and Elliott et al . ().…”
Section: Introductionmentioning
confidence: 87%
“…Our framework also differs from recent efforts directed at connecting network structure and the propagation of adverse shocks, which focus on the “contagion” of catastrophic events in specific sectors, such as bank failure (e.g., Acemoglu, Ozdaglar, and Tahbaz‐Salehi (), Elliott, Golub, and Jackson (), Gouriéroux, Héam, and Monfort (), among others) over just a few time periods. In contrast, our model generates long memory even from everyday shocks, and not just through rare catastrophic events, and makes specific predictions regarding the network's spectral response within an infinite‐horizon framework.…”
Section: Introductionmentioning
confidence: 99%